Visceral basidiobolomycosis: An overlooked infection in immunocompetent children - Parkash Mandhan; Kamal Osman Hassan; Sandra Moustafa Samaan; Mansour J Ali (Wolters Kluwer Medknow Publications, 2015)
Visceral basidiobolomycosis is an unusual fungal infection of viscera caused by saprophyte Basidiobolus ranarum. It is very rare in healthy children and poses a diagnostic challenge due to the non-specific clinical presentation and the absence of predisposing factors. We report a case of gastrointestinal basidiobolomycosis in a 4-year-old healthy girl who presented with a short history of abdominal pain, bleeding per rectum, fever, and weight loss. The diagnosis was based on high eosinophilic count, classical histopathology findings of fungal hyphae (the Splendore-Hoeppli phenomenon), and positive fungal culture from a tissue biopsy. Fungal infection was successfully eradicated with a combined approach of surgical resection of the infected tissue and a well-monitored course of antifungal therapy. The atypical clinical presentation, diagnostic techniques, and the role of surgery in the management of a rare and lethal fungal disease in an immunocompetent child are discussed.